Mass Transfer Coefficients and Correlation of Supercritical Carbon Dioxide Extraction of Sarawak Black Pepper - Ting, May; Then, Siew; Saptoro, Agus; Panau, Freddie (De Gruyter, 2013)
Bioactive compound, namely piperine, was extracted from Sarawak black pepper using supercritical carbon dioxide extraction. Experiments were carried out in the range of 3,000–5,000 psi (20.7–34.4 MPa) pressures, 318–328 K temperatures, 0.4–1 mm mean particle sizes and 5–10 ml/min carbon dioxide flow rates. Experimental data analysis shows that extraction yield is mainly influenced by pressure, particle size and coupled-interactions between these two variables. Extraction process was modeled accounting for intraparticle diffusion and external mass transfer. The kinetics parameters for the internal and external mass transfers were evaluated and estimated. Mass transfer correlation was also developed. From simulation results, good agreement between experimental and simulated data has been found.